Advances in Hypertension Management: Insights from the Latest European Guidelines - Marco Zuin; Chiara Tognola; Alessandro Maloberti; Gianfranco Parati; Stefania Angela Di Fusco; Vered Gil Ad; Donatella Armata; Chiara Dalla Valle; Furio Colivicchi; Claudio Bilato; Massimo Grimaldi; Fabrizio Oliva; et al. (Journal of Cardiovascular Development and Disease)
Arterial hypertension is one of the most common and preventable risk factors for cardiovascular disease and its related mortality. Currently, the prevalence of hypertension in different European countries appears to be around 30–45% of the general population, with a steep increase with ageing. Recent European guidelines have introduced novel recommendations for the management and treatment of hypertensive patients, with direct implications in daily clinical practice. Therefore, in this focused review, we will provide answers to the most common questions regarding the diagnosis, management and treatment of arterial hypertension according to the latest available European guidelines.